A 24-bp indel within the sheep AHR gene is associated with litter size. Issue 7 (12th December 2022) - Ren, Hongying; Tang, Qi; Xue, Tao; Wang, Qian; Xu, Hongwei; Zhang, Qingfeng; Pan, Chuanying
Abstract: Aryl Hydrocarbon Receptor (AHR) is a member of the PER-ARNT-SIM (PAS) family, which could mediate various biological processes, for instance, the balance of the immune system, cell proliferation, differentiation, vascular tissue remodeling and reproduction ability regulation. A previous research showed that the AHR gene exerted important functions on the pig reproduction, implying that it could serve as a candidate gene related to animal reproductive traits. Here, the aim of this work was to identify potential insertion/deletion (indel) mutations of the AHR gene in three sheep breeds and analyze the associations between these mutations and reproductive traits. Results showed that a 24-bp indel was uncovered three genotypes (II, ID and DD) in the Australian White sheep (AuW) and Lanzhou fat-tail sheep (LZFT) population, while there were only two genotypes (ID and DD) in Luxi black-headed sheep (LXBH). Moreover, the Fisher's exact test showed that the 24-bp indel mutation was significantly associated with litter size and live litter size in AuW sheep (Fisher's p  < 0.05). Therefore, the 24-bp indel of sheep AHR gene can contribute to sheep marker-assisted selection breeding and further improve the sheep reproductive performance.